DryadInc: Reusing work in large-scale computations - Budiu, Mihai; Yu, Yuan; Isard, Michael (Workshop on Hot Topics in Cloud Computing 2009 (HotCloud 09), 2009)
Many large-scale (cloud) computations operate on append-only, partitioned datasets. We present two incremental computation frameworks to reuse prior work in these circumstances: (1) reusing identical computations already performed on data partitions, and (2) computing just on the newly appended data and merging the new and previous results.